Estimation of Planar Trend Model Parameters for Midlatitude Ionosphere. Issue 2 (15th February 2020) - Kumbay Yildiz, S.; Arikan, F.
Abstract: Being under influence of the polar and equatorial regions, the midlatitude ionosphere poses an important challenge in structural modeling. In this study, the general understanding of regional planar trend model is investigated for 2011 by estimation of trend coefficients in the least squares sense. The northern midlatitude is divided into 24 nonoverlapping regions of 10° by 20° in latitude and longitude, respectively. The magnetic conjugates of 24 regions in the Southern Hemisphere are also extracted. The total electron content values are obtained from global ionospheric maps (GIM) with spatial resolution of 2.5° by 5° in latitude and longitude, respectively. The temporal resolution of GIM can be 1 or 2 hr. Estimated planar trend coefficients are used to reconstruct model maps. The difference between GIM and the estimated planar model is obtained in normalized L 2 norm squares sense. It is observed that the planar trend model in latitude and longitude is an agreeable model for total electron content over midlatitude regions for both Northern and Southern Hemispheres. The estimated model parameters generally follow the diurnal, seasonal, and semiannual trend structures of midlatitude ionosphere. The deviations from the model occur mostly during severe disturbances such as geomagnetic storms. The difference between the reconstructed model maps with estimated parameters and GIM is generally under 1% for land and 2% to 5% for ocean regions. The only region that has a very high spread and mostly up to 10% difference with the GIM throughout the year is on the California Current. Plain Language Summary: The manuscript contains a very comprehensive analysis of midlatitude planar trend structure for 2011. The coefficients of the model are estimated in the least squares sense from the global ionospheric maps. The results of the study indicate the validity of the locally linear trend of midlatitude ionosphere in both the Northern and Southern Hemispheres. The highest deviations from the planar model occurred during high variability of solar activity with multiple maxima of sunspot number, geomagnetic disturbances, for regions over the passage between different pressure zones, and the saddle structure longitude of main field intensity around 165° in geomagnetic longitude. Overall, for almost all land and for some ocean regions, the annual difference is under 2%. Even for the regions with higher variability, the difference is generally under 10%. Key Points: Planar trend model represents midlatitude GIM‐TEC successfully in both hemispheres Diurnal, seasonal, and semiannual periodicities are observed in planar model coefficients Estimated values of planar model coefficients and their spread increase during equinoxes